Patent Ductus Arteriosus - Putra Futtaqi; Aulia Mustika (Jurnal Anestesi, 2025)
Patent ductus arteriosus is one of the congenital heart disease caused by the failure of the ductus arteriosus to close after birth. The ductus arteriosus, a fetal blood vessel connecting the pulmonary artery and the aorta, typically closes within the first 1–3 days in term infants. In PDA, this condition can lead to excessive blood flow to the lungs and systemic hypoperfusion. The incidence of PDA varies, occurring in 0.3–4 per 1,000 live births, and accounts for 5–10% of congenital heart defects. The risk increases with preterm birth, particularly at gestational ages of less than 30 weeks. The younger the gestational age at birth, the higher the risk of PDA. Management of PDA aims to close the ductus arteriosus or alleviate symptoms through conservative therapy, pharmacological treatment, or surgery. By understanding the etiology, prevalence, and therapeutic approaches to PDA, better management strategies can be implemented to minimize complications in newborns.